Seasonal shifting and its impact on crop production: local community perception of Satkhira district (BRAC University Journal, 2026)
In Bangladesh, climate change apparently has started to affect the climatic parameters which cause seasonal shifting and the behavior of different seasoos. This kind of pheoomeoon is currently posing a serious threat to the agricultural crop production and food security of the coun1ry. Participatory Rural Appraisal method was applied to investigate the perception of the local commnnity of Satkhira district. The study primarily ideotified the thinking of the local people about the shifting of seasons due to changes in the climatic parameters and its impact on crop production. Moreover, a number of literatures were reviewed to conceptualize the real scenario of climate change. Preseotly, ooly three seasons are perceived by the local community instead of the traditional six seasons. These seasonal fluctuations (starting and ending) and seasonal absences are resulting in high nncertainty in crop production. New agricultural plan along with climate resilient agricultural extension services need to be introduced to overcome such uncertainty.